Support for lowering cervical cancer screening age to 25 for women living with HIV: retrospective cross-sectional programmatic data from Botswana - Doreen Ramogola-Masire; Surbhi Grover; Anikie Mathoma; Barati Monare; Lesego Gabaitiri; Lisa Bazzett-Matabele; GJustus Hofmeyr; Chelsea Morroni; Rebecca Luckett (BMC, 2022)
Abstract Background Women living with human immunodeficiency virus (HIV) tend to develop cervical cancer at a younger age than women without HIV. The World Health Organization's (WHO) 2021 guidelines for screening and treatment of cervical pre-cancer lesions for cervical cancer prevention include a conditional recommendation for initiating screening at age 25 for women living with HIV (WLWH). This recommendation is based on low-certainty evidence, and WHO calls for additional data. We describe the association of age and HIV status with visual inspection with acetic acid (VIA) positivity and cervical intraepithelial neoplasia grade two or higher (CIN2+) in Botswana. Methods This was a retrospective cross-sectional study of 5714 participants aged 25 to 49 years who underwent VIA screening in a clinic mainly serving WLWH. VIA-positive women received cryotherapy if eligible or were referred for colposcopy and excisional treatment. Known cervical cancer risk factors, screening outcome, and histological results were extracted from the program database. We compared the proportions and association of VIA positivity and CIN2+ by age and HIV status. Results The median age was 35 years [IQR 31-39], and 18% of the women were aged 25-29. Ninety percent were WLWH; median CD4 count was 250 cells/µL [IQR 150-428], and 34.2% were on anti-retroviral treatment (ART). VIA-positivity was associated with younger age (OR 1.48, CI 1.28, 1.72 for 25-29 years vs. 30-49 years), and HIV-positivity (OR 1.85, CI 1.51, 2.28). CIN2+ was only associated with HIV-positivity (OR 6.12, CI 3.39, 11.10), and proportions of CIN2+ were similar for both age groups in WLWH (69.1% vs. 68.3%). Conclusions Younger WLWH in Botswana had a significant burden of CIN2+. This finding further supports lowering the screening age for WLWH from 30 to 25.